Analisis Pengaruh Pengetahuan Struktur Kalimat Terhadap Kemampuan Literasi Membaca Mahasiswa Universitas Merdeka Malang - Ulla A.J, Nasikhatul; Khasanah, Ismatul; Khasanah, Ismatul (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
Reading literacy in Indonesia has been very low, and factors contributing to low literacy have not been resolved. This study aims to analyze the relationship of sentence structure knowledge in reading literacy skill (1), the contribution of sentence structure knowledge in reading literacy skill (2). This study employed mixed method design of quantitative and qualitative method. Quantitative design was used to address reaseach purpose 1 and 2 particularly using correlations and regression analyses to explain the relationship.                             Participants of this study were53 students of the Merdeka University of Malang. Data were collected from Indonesian Language Proficiency Test (Ujian Kemahiran Berbahasa Indonesia/UKBI) and a reading interest questionnaire completed byparticipants.  This study revealed that there was a significant positive relationship between sentence structure knowledge and reading skills, r= .294, p = .034. The contribution of sentence structure knowledge accounted for 8,6% of reading literacy variance. This study provides support for Indonesian teachers and tutor to develop students’ Indonesia sentence structure knowledge and to arouse their reading interests.